TANGGUNG JAWAB HUKUM PERDATA DALAM TRANSAKSI DIGITAL: ANALISIS KONTRAK ELEKTRONIK, PLATFORM MARKETPLACE, DAN PERLINDUNGAN KONSUMEN DI INDONESIA - Sendi Sanjaya (Berajah Journal, 2025)
Digital transformation has fundamentally changed economic transaction patterns in Indonesia, requiring adjustments to the concept of civil liability for electronic contracts and the role of marketplace platforms. This study analyses the normative basis and civil law practices in digital transactions, focusing on the validity of electronic contracts according to the Civil Code and Law 11 of 2008 on Electronic Information and Transactions, as well as the responsibility of marketplace platforms for consumer losses within the framework of Law No. 8 of 1999 on Consumer Protection and Government Regulation No. 80 of 2019 on Trading Through Electronic Systems. This research uses a normative (juridical-dogmatic) legal approach with an analysis of legislation, doctrine, and case studies of online transactions. The results of the study show that electronic contracts are normatively recognised as valid and binding, but in practice there is still uncertainty regarding evidence, authentication, and standard clauses that are detrimental to consumers. On the other hand, marketplace platforms have preventive, contractual, and repressive responsibilities towards consumers, but in many cases, these responsibilities are still limited to administrative and technical aspects, so the concept of joint liability between marketplaces and sellers needs to be strengthened. This article concludes that there is a need for further harmonisation between civil law, digital regulations, and consumer protection to ensure fairness, legal certainty, and balanced protection in the digital transaction ecosystem in Indonesia.